Development of microsatellite loci in zoonotic tapeworm Dibothriocephalus latus (Linnaeus, 1758), Lühe, 1899 (syn. Diphyllobothrium latum) using microsatellite library screening - Bazsalovicsová, Eva; Koleničová, Alžbeta; Králová-Hromadová, Ivica; Minárik, Gabriel; Šoltys, Katarína; Kuchta, Roman; Štefka, Jan (Molecular and biochemical parasitology, 2018)
The broad fish tapeworm Dibothriocephalus latus is a causative agent of human food-borne disease called diphyllobothriosis. Medical importance, scattered geographical distribution and unknown origin of D. latus in Europe and North America make this species to be an interesting model for population genetics. Microsatellite markers were originally designed by library screening using NGS approach and validated as tools for future studies on population genetics of D. latus. Out of 122 candidates selected after NGS analysis, 110 yielded PCR products of the expected size, and in 78 of them, a declared repetitive motif was confirmed by Sanger sequencing. After the fragment analysis, six loci were proved to be polymorphic and tested for observed (Ho) and expected (He) heterozygosity, and deviations from Hardy-Weinberg equilibrium (HWE). They promise future application in studies on genetic interrelationships, origin and migratory routes of this medically important emerging tapeworm.
Keywords: Microsatellites; Europe; mikrosatelitní repetice; Severní Amerika; genotypizační techniky; Evropa; populační genetika; genetická variace; Population genetics; Genetics, Population; Microsatellite Repeats; North America; Genotyping Techniques; Diphyllobothriidea; Genetic Variation; zvířata; Short tandem repeats; Broad Fish tapeworm; Diphyllobothrium; Animals